2015
DOI: 10.1002/star.201500077
|View full text |Cite
|
Sign up to set email alerts
|

A novel saccharifying α‐amylase of Antarctic psychrotolerant fungi Geomyces pannorum: Gene cloning, functional expression, and characterization

Abstract: A DNA segment encoding a novel a-amylase was cloned from the Antarctic psychrotolerant fungi Geomyces pannorum. The gene has an open reading frame of 1761 bp, deduced 586 amino acids, revealing a relatively low homology to a-amylases from diverse fungal genera. The a-amylase gene was overexpressed in Pichia pastoris, and the recombinant a-amylase was purified and characterized. Enzymatic activity was optimal at pH 6.0 and 70°C, and the specific activity was 9.78 Â 10 3 U/mg when using soluble starch as substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…Antarctic fungal strains representative of the genera Cryptococcus, Dioszegia, Glaciozyma, Holtermaniella, Leuconeurospora, Mrakia, Moesziomyces, Penicillium, Pseudogymnoascus, Rhodotorula, Phenoliferia, and Thelebolus were reported to be amylase producers [12,13,32,[62][63][64][65]99,118]. Amylase activity has been assayed by growing the selected strains on media supplemented with starch as a carbon source.…”
Section: A-amylases and Glucoamylasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Antarctic fungal strains representative of the genera Cryptococcus, Dioszegia, Glaciozyma, Holtermaniella, Leuconeurospora, Mrakia, Moesziomyces, Penicillium, Pseudogymnoascus, Rhodotorula, Phenoliferia, and Thelebolus were reported to be amylase producers [12,13,32,[62][63][64][65]99,118]. Amylase activity has been assayed by growing the selected strains on media supplemented with starch as a carbon source.…”
Section: A-amylases and Glucoamylasesmentioning
confidence: 99%
“…Therefore, the expression must be performed in other eukaryotic organisms; P. pastoris appears to be a good host for fungal cold-adapted enzyme expression. According to Gao et al [64], the a-amylase from Pseudogymnoascus pannorum R2-1 (formerly Geomyces pannorum) cloned in P. pastoris presented low homology to other a-amylases, with thermophilic characteristics (optimal activity at 70.0 C). In another study, Ramli et al [68] reported that the chitinase from G. antarctica PI12 expressed in P. pastoris was most active at 15.0 C, being stable in the range of 5.0-25.0 C. According to Feller and Gerday [58], a great contribution in this field could be associated with the use of a psychrophilic microorganism as a host for the expression of genes at low temperatures, preventing the formation of inclusion bodies and protecting heat-sensitive gene products.…”
Section: Heterologous Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…To meet the increasing demands of biocatalytic tasks, extensive efforts have been made to isolate enzymes produced by extremophiles, owing to their special properties and significant potential economic values (González-Segura, Witte, McClard, & Hurley, 2007 ;Piette, Struvay, & Feller, 2011 ;Ueda et al, 2014 ). However, limited attention has been paid to the identification and characterization of these APs (Gao, Mao, Zhang, He, & Wei, 2016 ;Kasana & Gulati, 2011 ;Krishnan, Alias, Wong, Pang, & Convey, 2011 ;Mao et al, 2015 ).…”
mentioning
confidence: 99%